2009
DOI: 10.1158/0008-5472.can-08-4977
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise DNA Methylation Changes Are Linked to Escape from Defined Proliferation Barriers and Mammary Epithelial Cell Immortalization

Abstract: The timing and progression of DNA methylation changes during carcinogenesis are not completely understood. To develop a timeline of aberrant DNA methylation events during malignant transformation, we analyzed genome-wide DNA methylation patterns in an isogenic human mammary epithelial cell (HMEC) culture model of transformation. To acquire immortality and malignancy, the cultured finite lifespan HMEC must overcome two distinct proliferation barriers. The first barrier, stasis, is mediated by the retinoblastoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
143
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 42 publications
(81 reference statements)
3
143
0
Order By: Relevance
“…The postselection HMEC used thus far have overcome stasis, the stress-associated senescence barrier, by selecting for p16 promoter methylation (3). In that process, they also acquired additional aberrant properties, including numerous DNA methylation changes (3,27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The postselection HMEC used thus far have overcome stasis, the stress-associated senescence barrier, by selecting for p16 promoter methylation (3). In that process, they also acquired additional aberrant properties, including numerous DNA methylation changes (3,27).…”
Section: Resultsmentioning
confidence: 99%
“…In that process, they also acquired additional aberrant properties, including numerous DNA methylation changes (3,27). We thus extended this work by examining normal, prestasis HMEC transduced with an shRNA targeting p16; this population does not express the aberrant methylation seen with the postselection HMEC (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Experiments using human cell lines have shown that genomewide DNA methylation of promoter CpG islands increases during the process of immortalization, 27,28 and most recently, this result was confirmed in mouse embryonic fibroblasts. 29 To determine whether the genome-wide DNA hypermethylation of promoter CpG islands that occurs in mouse cells during the process of immortalization is more similar to human cancers than the modest methylation changes observed in GEMMs, we created newly immortalized mouse fibroblasts by serially passaging primary cells in vitro and selecting clones that spontaneously acquired the ability to bypass replicative senescence.…”
Section: Mouse Fibroblasts Passaged Through Crisis Obtain Extensive Gmentioning
confidence: 92%
“…Cultured HMEC have been employed in a wide variety of studies examining the normal processes governing growth, differentiation, aging, and senescence, and how these normal processes are altered during immortal and malignant transformation [4][5][6][7][8][9][10][11][12][13][14][15]16 . The effects of growth in the presence of extracellular matrix material, other cell types, and/or 3D culture can be compared with growth on plastic 5,15 .…”
mentioning
confidence: 99%